The Effect of Imagery Training on Increasing the Confidence of Hockey Athletes - Nursaba, Siti; Sidik, Dikdik Zafar; Tafaqur, Muhamad; Mulyana, Mulyana (Universitas Majalengka, 2024)
This study aims to determine the effect of imagery training on increasing the confidence of hockey athletes. The research subjects consisted of 18 athletes who were members of a hockey academy in Bandung City. The research design used was one group pretest-posttest, where the subjects were given an initial test to measure the level of self-confidence before being given treatment in the form of imagery training. The imagery training program lasted for 8 sessions, with a duration of 50 minutes per session. After the program was completed, a final test was conducted to measure the increase in self-confidence using a questionnaire that had been tested for validity. The results of the analysis with paired t-test through SPSS 26 showed a significant increase in the level of self-confidence of athletes after undergoing imagery training. this is evidenced by all charts having increased after being given imagery training with an average difference of 7%. This study concludes that imagery training is recommended to be applied in the world of sports because this exercise can help athletes perform optimally when athletes have confidence